PERENCANAAN BENDUNGAN MANONJAYA KABUPATEN TASIKMALAYA, JAWA BARAT - Muhammad Qorib Hidayat; Kalih Amanis Shofa; Sri Eko Wahyuni; Suseno Darsono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Increasing water demand is caused of increasing population at Tasimalaya Regency, inversely with water supply to that area. This problem is solved by constructing a reservoir located in Tasikmalaya regency, West Java that is the Manonjaya Dam. Manonjaya Dam is a earthfill dam with a vertical core which is built at Citanduy River with 590.422 km2 of catchment area. This aims of dam to fulfill public water supply and irrigation at Tasimalaya Regency. Manonjaya Dam is designed with 100 years of return period with inflow discharge valued 513.9 m3/second. Manonjaya Dam is designed 23.5 meters of height, with 3,9 million cubic meters of capacity. The dam has equipped with 3,5 meters of diameter outlet pipe, spillway with 30 meters of width, and USBR III of stilling basin. Construction cost of Manonjaya Dam is around 154 billion Rupiahs with scheduled for 33 weeks.